Holistic Education by breaking the binaries beyond the boundaries - et. al., Ignisha Rajathi G, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The educational system currently prevailing across the globe is of divergent genre. Education has become the prime focus among all the intelligentsia and educationalists. The efforts of the regime in nurturing the system, the cartel of government and private Institutions are the issues that keep bouncing back. And now the Pandemic crisis has been an extreme threat that signifies the importance on social distancing. So, with the shut off of the knowledge sharing, with direct contact has ignited the quest for seemingly establishing a virtual environment to feed the thirst for intellectual wisdom. Irrespective of infrastructure, accessibility to the external virtual environment has been a strong fervent desire of the current days of each one. It is beyond boundaries through online webinars, virtual classrooms, Learning Management Systems, video lecture uploaded anywhere and everywhere. This has provided a hustle free environment for all students except for the economically conducive regional folks to reach the remote Education. Various methodologies pertaining to remote education and the simplified approaches are discussed in this paper. And the concern to reach the unreached has been a visionary of discussion in this research through simple messaging service through mobile phones.